Perioperative Outcomes of Inguinal Hernioplasty along with Holmium Laser Enucleation of the Prostate (HoLEP) - Calvo de la Barra, Carlos Ignacio; Bravo Izurieta, Juan Cristobal; Navarro Capone, Renato; Cañas Ramirez, Rodrigo; Pasten Alcaina, Felipe; San Francisco Reyes, Ignacio (Urology Journal, 2023)
Purpose: Inguinal hernias and benign prostatic hyperplasia (BPH) can coexist in about one fifth of patients undergoing BPH surgery. There is scarce evidence about performing laser enucleation along with open inguinal hernia repair. Our goal is to describe the perioperative outcomes of performing both surgeries in the same operating session compared to doing HoLEP alone. Materials and Methods: A retrospective analysis of patients undergoing HoLEP and hernioplasty with mesh in the same anesthetic time (group B) at an academic center was conducted. They were compared to a randomly picked control group of patients submitted to HoLEP alone (group A). Preoperative, operative and postoperative features were compared among both groups. Results: 107 patients submitted to HoLEP alone were compared to 29 combined approach patients (HoLEP + hernia repair). Patients in group A were found to be older and had larger prostates. Group B showed a significant longer operative time. Length of stay and duration of catheter was comparable among groups. In multivariate analysis, the combined approach was not associated to a higher complication rate. Conclusion: Performing benign prostatic hyperplasia surgery with HoLEP in conjunction with open inguinal hernioplasty is not related to a higher length of stay or a significantly increased risk of morbidity.